Systematic Riview : Intervensi Upaya Preventif Infeksi Menular Seksual Berbasis Komunitas Pada Populasi Beresiko - Anarkie, Bella (Universitas Dehasen Bengkulu, 2025)
Background: Sexually transmitted infections (STIs) are infections that are mostly transmitted through sexual intercourse with an infected partner. STIs are also known as sexually transmitted diseases. Sexually transmitted infection is a general term and the causative organisms live in the blood or body fluids, including viruses, microplasma, bacteria, fungi, and small parasites. There are approximately 30 types of microbes (bacteria, viruses and parasites) that can be transmitted through sexual and non-sexual contact. The most common conditions are gonorrhea, chlamydia, genital herpes, human immunodeficiency virus (HIV) infection and trichomoniasis.Study Objectives: To find out community-based prevention of sexually transmitted infections in at-risk populations. Methodology: Analysis using a systematic review analysis approach that uses 50 national and international journals uploaded through Google Scholar and PubMed from 2015-2021. Research results: The factors most related to the incidence of sexually transmitted infections and at the same time population-based at risk are internal factors in the form of knowledge about STIs, commercial sex workers, marital status, attitudes, age, LGBT, nightlife workers, drug users, and free sex without using condom. While external factors are family support, environment, peers and lack of education. Suggestion: Based on the results of a study from 50 journals that researched that sexually transmitted infections and risk groups for sexually transmitted infections, almost all results stated that the most vulnerable sexually transmitted infections were groups with less knowledge about STIs, commercial sex workers, marital status, attitudes, age, LGBT, night workers, drug users, and free sex without using a condom. Therefore, this matter must be considered by the relevant agencies to increase the provision of education to the public related to the problem of this sexually transmitted infection.